Electrochemical Approach on Mechanism of an Oral Progestin in Aqueous Media and its Fully Validated Detection via a Carbon-Metal Based Composite Sensor - ÇELİK, MELEK ŞİRİN (WILEY-V C H VERLAG GMBH, 2018)
Dienogest is a synthetic oral progestogen with unique pharmacological properties that is used orally in the treatment of endometrosis. The first time, the detailed electrochemical mechanism of dienogest is investigated in different aqueous mediums. Different progestins were used to understand completely oxidation mechanism. The electrochemical oxidation of dienogest was investigated systematically by cyclic voltammetry, differential pulse voltammetry, and square wave voltammetry. A simple adsorptive stripping square wave voltammetry method has been developed for the fully validated direct determination of dienogest in Visanne Tablets for the first time. Nano based sensor was fabricated with reduced graphene oxide, gold and carboxylic acid functionalized multi-walled carbon nanotube materials, and were used on glassy carbon electrode that performed sensitive and validated analysis of dienogest by adsorptive stripping square wave voltammetry. Validation parameters were investigated in detail. The results yielded good precision, accuracy and reproducibility. Calibration range was found as 2.00x10(-7)M to 6.00x10(-6)M, with LOD and LOQ values as 1.88x10(-8)M and 6.27x10(-8)M, respectively. In the future, the developed sensor can be applied in different media such as environment, soil and water for the detection of some progestins or hormones by researchers.
Keywords: Dienogest; Oxidation; Square Wave Voltammetry; Validation; Surface Modified Electrode; GRAPHENE OXIDE; ORGANIC-SOLVENT; HUMAN PLASMA; DIENOGEST; DIHYDROXYLATION; QUANTIFICATION; NANOPARTICLES; OXIDATION; OLEFINS